Analisis Operasi Pemberian Air Irigasi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Irrigation water requirement of paddy fields can be supplied either by rainfall (effective rainfall) and or irrigation water. Effective rainfall is the amount of rainfall which is useful directly for crops production. Accuracy in providing irrigation water depends on various factors, such as the effective rainfall, irrigation efficiency, climate, and kinds of the crops. Operation of intake gate by operator generally depends on water requirement requested by the farmers (P3A) of tertiary block and existing irrigation efficiency. Accurate amount of irrigation water requirement and irrigation efficiency should be analyzed based on the field condition. Many countries have developed effective rainfall as one of the component in providing irrigation water requirement. Indonesia has applied the effective rainfall analysis based on the historical rainfall data (Ministry of Public Works, 1986). Other method for computing effective rainfall used in this study are the India method dan Renfro method. The practice of operation of intake gate carried out by the operator based on the farmers request and the performance of irrigation network system in PB5-ka block of Pijenan command area in Bantu! Regency are analyzed based on the field condition and effective rainfall calculated under the three methods. Analysis results show that the irrigation network system efficiencies in BP5-ka block during the cultivation period (MT) II, I, and III are good (70%), fair (50%) and poor (20%), respectively. Such conditions indicate that the irrigation network efficiency based on the Ministry of Public Works standard (80%-85%) is excessive and required adjustment to the field condition. The practice of operation of intake gate carried out by the operator appears to be wasteful at the end of MT I, II, and III, which is more than 80%. However, in total average it has fulfilled the accurate amount criteria with surplus tolerance of 2.57%, 1.32% and 12.50%, respectively. Based on the cultivation period 2002-2003 as well as the soil type of BP5-ka block, the irrigation water reqirement (effective rainfall calculated using the Ministry of Public Works method, Renfro method, and India method) should be theoretically modificated